Libraries in the Community: Changing Opportunities - Zurinski, Stephanie; Osborne, Valerie; Anthoine-Ney, Mamie; McKenney, Janet (Maine Policy Review, 2013)
When libraries first began, books were scarce and expensive. We live now in the Information Age. Public expectations about information are rapidly evolving. To remain relevant, libraries are expanding on sociologist Ray Oldenburg’s “Third Place” concept – public spaces which are “anchors of community life and important places for civic engagement”. Libraries have always offered a place for the community to come together. Now, libraries are becoming destinations by offering experiences ranging from the traditional story-telling to creation spaces and business incubators. Even with all the changes occurring in the world, libraries will remain the glue that holds the community together.
Keywords: Maine; libraries